Valery Gergiev conducts Prokofiev Alexei Volodin performs the 4th piano concerto : Moscow Easter Festival - Prokofiev, Sergey 1891-1953; Prokofiev, Sergey 1891-1953; Prokofiev, Sergey 1891-1953; Prokofiev, Sergey 1891-1953; Prokofiev, Sergey 1891-1953; Prokofiev, Sergey 1891-1953 (Idéale Audience, 2012)
At the Moscow Easter Festival, Valery Gergiev and the Mariinsky Theatre Orchestra invite pianist Alexei Volodin. The Mariinsky Theatre Orchestra and their music director Valery Gergiev play the Symphony No. 4 as well as excerpts from the ballet Cinderella and the rarely performed Egyptian Suite. For this performance, the festival invited Alexei Volodin, a pianist from St. Petersburg like the orchestra, and a former student of Elisso Virsaladze at the Moscow Conservatory, where he now plays the Piano Concerto No. 4 "for the left hand" by Prokofiev, a work of extreme difficulty. Starting each year on Easter Sunday (according to the Julian calendar), the Moscow Easter Festival features great concerts with the Mariinsky Theatre Orchestra and music director Valery Gergiev, but also internationally renowned soloists. In 2012, the festival -- dedicated to Sergei Prokofiev -- invited the pianists Daniil Trifonov (1st prize at the Tchaikovsky Competition in 2011 and third prize at the Chopin Competition in 2010), Alexander Toradze (familiar to Gergiev), Alexei Volodin (a former student of the Moscow Conservatory) and the American-Armenian pianist Sergei Babayan. Over the past 20 years spent at the head of the Mariinsky Theatre Orchestra, Valery Gergiev has clearly opened one of the most prestigious Russian orchestras' repertoire. Their interpretations of Prokofiev have become legendary, not only because Gergiev has recorded most of the composer's masterpieces, but also because he has contributed in promoting the rarest pieces Prokofiev has ever written. This series of concerts, programmed as part of the 11th anniversary of the Moscow Easter Festival, display complete Prokofiev symphonies, but also four of his Piano concertos, along with excerpts from the composer's great ballets (Cinderella and Romeo and Juliet). This concert was broadcast live on medici.tv
Keywords: Ballets; Concertos (Piano, 1 hand); Sonatas (Piano); Symphonies; Ballets -- Excerpts; Internet videos